Bangla optical character recognition from printed text using Tesseract Engine - Faruque, MD Yamin; Adeeb, MD Zahin; Kamal, Muhammad Maswood; Ahmed, Redwan (Brac University, 2021)
Cataloged from PDF version of thesis.